Effects of Energy Consumption on Growth in Eurasian Countries - Bildirici, Melike; Kayikci, Fazil (ELSEVIER SCIENCE BV, 2016)
Some Eurasian countries play major roles in the world energy market as producers of oil and natural gas as well as being energy distribution centers. However, energy intensities of these countries are also very high compared to other transition countries in the world. This study aims at analyzing the relationship between energy consumption and economic growth in Eurasian Countries for 1992-2010 period. Empirical results reveal that energy consumption and economic growth are cointegrated for these countries. Furthermore, there is positive bidirectional causality between energy consumption and economic growth in the long run which supports the feedback hypothesis. Hence, policymakers in the Eurasia region should consider improving the energy infrastructure and increasing the energy supply to achieve higher economic growth when designing energy policies, whereas energy conservation policies should not be implemented for these countries since it may negative effect on economic growth. (C) 2016 The Authors. Published by Elsevier B.V.
Keywords: Growth; Causality; Cointegration; Energy Consumption; Eurasian Countries; Energy Policies; UNIT-ROOT TESTS; ELECTRICITY CONSUMPTION; ECONOMIC-GROWTH; REAL INCOME; PANEL-DATA; Business & Economics